Software Quality Analysis using the ISO 25010 Standard on the Digital Information System of the Blitar City Government - Diajeng Putri Widiastuti; Nur Cahyo Wibowo; Eka Dyar Wahyuni (JASIEK (Jurnal Aplikasi Sains, Informasi, Elektronika dan Komputer), 2025)
The Online and Integrated Personnel Information System (SIKOI) was developed by the Regional Civil Service and Human Resource Development Agency (BKPSDM) to manage the administrative data of approximately 3,200 employees in the City of Blitar. As the system is still under development, this study aims to evaluate the quality of the SIKOI application using the ISO/IEC 25010 standard, which covers both functional and non-functional aspects. The research methods include direct observation and literature review regarding software quality standards. The evaluation was conducted across seven key characteristics: functional suitability, performance efficiency, compatibility, usability, reliability, security, and portability. The results of this study provide insights into the system’s quality and assist system managers in formulating appropriate improvement measures. SIKOI is considered sufficiently feasible to support personnel management in Blitar City; however, several aspects still require improvement in order to fully optimize its overall performance.